Strategi Pendidikan Kepribadian di Pondok Modern Darussalam Gontor Putri Kampus 2 Sambirejo Mantingan Ngawi - Abu Darda; Luthfiyatin Nahriyah; Puji Asmaul Chusna; Moh. Alqhoswatu Taufik; Lailatul Mubaarokah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The adolescent identity crisis, characterised by a decline in moral standards and weak self-control, poses a serious challenge for Islamic educational institutions, prompting Pondok Modern Darussalam Gontor Putri Campus 2 to develop a character education programme focused on fostering an Islamic character that is action-oriented. This study aims to analyse the character education strategies implemented and the factors supporting them. The research employs a qualitative approach using field research, with data collection techniques comprising observation, interviews, and documentation, as well as data analysis through data reduction, data presentation, and drawing conclusions. The research findings indicate that character education strategies are implemented through guidance, training, habit formation, assignments, supervision, and exemplary behaviour (uswah hasanah), which are applied consistently. Supporting factors for the character development of female students include the formation, application, and development of character, reinforced by the boarding school’s culture of discipline. These findings indicate that personality education strategies integrated with the institution’s values and culture are effective in shaping the Islamic personality of female students and have the potential to be adapted by other educational institutions with adjustments to the environmental context.